Isolating the effects of ontogenetic niche shift on brain size development using pumpkinseed sunfish ecotypes. Issue 4 (11th March 2020) - Axelrod, Caleb J.; Laberge, Frédéric; Robinson, Beren W.
Abstract: A functional relationship between relative brain size and cognitive performance has been hypothesized. However, the influence of ontogenetic niche shifts on cognitive performance is not well understood. Increases in body size can affect niche use but distinguishing nonecologically relevant brain development from effects associated with ecology is difficult. If survival is enhanced by functional changes in ecocognitive performance over ontogeny, then brain size development should track ontogenetic shifts in ecology. We control for nonecologically relevant brain size development by comparing brain growth between two ecotypes of Pumpkinseed sunfish whose ecologies diverge over ontogeny from a shared juvenile niche. Brain size differs between ecotypes from their birth year onwards even though their foraging ecology appears to diverge at age 3. This finding suggests that the eco‐cognitive requirements of adult niches shape early life brain growth more than the requirements of juvenile ecology. Abstract : We tested the hypothesis that changes in brain size are partially caused by a response to ontogenetic niche shift using coexisting ecotypes of pumpkinseed sunfish. This figure illustrates the result that while ecotypes diverge in ecology over ontogeny from a shared juvenile niche (dashed lines), contrary to our expectations, brain size diverges in the first year of life (solid lines) well before any indication of ecological differentiation. This is strong evidence that the ecological divergence of adult sunfish has shaped the evolution of brain growth trajectories more so than ontogenetic shifts in ecology. Research Highlights: Brain size development precedes ontogenetic niche shift in coexisting sunfish ecotypes. We conclude that in this system adult ecology has shaped the evolution of brain growth trajectories rather than ontogenetic shifts in ecology.